Exploring barriers to colorectal cancer screening in Saudi Arabia: findings from a cross-sectional study - Busbait, Saleh (Frontiers in Public Health, 2025)
BackgroundColorectal cancer (CRC) is a leading cause of cancer-related morbidity and mortality worldwide. Despite national screening recommendations, CRC screening uptake remains low in Saudi Arabia. This study aims to identify perceived barriers to CRC screening and examine their demographic variations.MethodsA cross-sectional study was conducted with 412 adults in the Eastern Province of Saudi Arabia. The study was conducted between April 2024 and July 2024 using a self-administered questionnaire. Perceived barriers to CRC were assessed using a questionnaire adapted from prior published studies. Statistical analyses included chi-square tests, exploratory factor analysis (EFA), and logistic regression to determine demographic predictors of screening barriers.ResultsThe most frequently reported barriers clustered into three domains: Personal Fears, Lack of Knowledge, and Healthcare System Barriers. “Absence of symptoms” (61.9%) and “fear of results” (28.9%) loaded under Personal Fears; “lack of awareness” (39.1%) under Lack of Knowledge; and “insufficient public awareness campaigns” (35.7%) under Healthcare Barriers. Women more commonly reported fear-related concerns, while younger participants cited knowledge gaps and financial limitations. The three factors explained 77.6% of the total variance. Logistic regression indicated that younger age and lack of prior screening experience were significant predictors of higher perceived barriers (p < 0.05).ConclusionThe findings highlight the need for targeted interventions addressing psychological concerns, increasing public awareness, and improving healthcare provider engagement. Addressing these barriers through structured awareness campaigns, provider-driven screening initiatives, and improved access to non-invasive screening options could increase CRC screening rates and early detection in Saudi Arabia.